OPEN FOR PROMPTS, OPEN FOR FILLS: CREATIVE DEPLOYMENT OF SOCIAL NETWORK SITES INTO FANDOM KINK MEMES - Neill Hoch, Indira (AoIR Selected Papers of Internet Research, 2014)
Profile-centric social network sites, including but not limited to Facebook, offer platforms for online communication that make core assumptions about how users want, or should want, to display information and perform identity. These assumptions can guide what is and is not distributed between users. The ease of use social network sites offer may prevent users from thinking critically about the kind of interactions they are performing. Creative deployment of existing social network site architecture offers the possibility for users to define the online experience they want, rather than the one they are told they should have. The social network site calls out, make a profile! Add friends! Subscribe! Follow! However, these commands, both written on the interface and coded in the structure of the site, can be used differently, against their intent. This paper considers fandom kink memes as creative deployments of LiveJournal.com and Delicious.com architecture. In creative deployment, fandom participants refashion an online space out of a preexisting site, crafting a social space that does not formally exist prior to intervention on the part of participants. Kink memes are a collective, anonymous space for requesting, distributing, and encouraging fan fiction. Participants are not permitted to post to the meme while logged into their LiveJournal.com accounts and the Delicious.com account is collectively maintained. Instead of undertaking the resource intensive project of developing a new social network or archive site, kink meme participants fashion the social experience they desire out of the architectural idiosyncrasies of existing online platforms. Indeed, the flexibility found in the LJ architecture means that the site continues to be used, even as other members of the user-base have moved on to other platforms. LJ continues to be relevant because of architectural elements not found in other sites. The meme is a playful and purposeful rearrangement of existing resources. This paper is rooted in careful textual and formal analysis of the visual and interactive aspects of the LiveJournal.com interface, the Delicious.com interface, and kink memes constructed from these two sites. The Dragon Age Kink sites (http://dragonage-kink.livejournal.com/ and http://www.delicious.com/dragonage_kink) are used as the basis for formal analysis of how kink memes are fashioned on each platform.